Synthesis and Characterization of Pb(II) complexes of Macrocycles Derived from 2,3-butanedione or Benzil and 1,n-Diaminaoalkanes - Parihar, D.S. (Asian Journal of Chemistry, 2010)
2,2-Cyclocondensation of 2,3-butanedione or benzil with 1,n-diaminoalkanes viz. 1,2-diaminoethane, 1,3-diaminopropane, 1,4-diaminobutane, 1,6-diaminohexane, 1,8-diaminooctane, 1,12-diaminododecane in the presence of Pb(ClO4)2·3H2O resulted in the formation of a new class of tetraazamacrocylic complexes. The use of Pb2+ as a template agent gave only the mononuclear macrocyclic complexes of the type [PbLClO4]ClO4 under all conditions investigated. These were characterized by elemental analyses, conductivity measurements and spectral studies.